The Effect of Compensation and Work Environment on Employee Performance Through Job Satisfaction t Ud. Efiyanto, Medan City - Waruwu, Dwi Putri Julianis; Prayoga, Boby Indra; Rambe, Saima (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Employee performance plays a crucial role in achieving organizational goals. To enhance performance, companies must consider various influencing factors, including compensation and work environment. Moreover, job satisfaction serves as a key element that can mediate these influences. This study aims to determine the effect of compensation and work environment on employee performance, both directly and indirectly through job satisfaction as an intervening variable at UD. Efiyanto in Medan City. This research employed a quantitative approach using descriptive and verificative methods. The population consisted of all 40 employees of UD. Efiyanto, using a saturated sampling technique. Data were collected through questionnaires and analyzed using path analysis with the aid of SPSS version 25. The results show that compensation contributes 93.2% and the work environment 95.5% to the improvement of employee performance. Additionally, compensation and work environment respectively influence job satisfaction by 35.4% and 8.2%, while job satisfaction contributes 9% to employee performance. This implies that when a company provides fair compensation and a comfortable work environment, job satisfaction increases and significantly impacts performance. Furthermore, F-test results indicate that compensation and work environment simultaneously have a significant effect on performance through job satisfaction, with contributions of 93.7% and 95.4%, respectively. Based on these findings, the company should pay attention to equitable compensation policies and foster a supportive work environment to ensure employee satisfaction and optimal performance.